Endometrial stromal sarcoma with Cd56 expression: a case report - Azizan N,; Hayati F,; Madatang A,; Abu Seman F, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Endometrial stromal sarcoma (ESS) is a rare malignant tumour of the endometrium, accounts for less than 1% of all uterine malignancies. Routinely, it is diagnosed morphologically, supported by immunomarkers of CD10 and vimentin. CD56 is used widely in neuroendocrine tumour. In our current practice, CD56 is not used to support the diagnosis of ESS. We present a case of a postmenopausal lady with advanced ESS who had expression of CD56 upon immunohistochemical study.